Actuation requirements of an active tendon concept in rotorcraft - Ondra, V.; Dibble, R.P.; Titurus, B.; Woods, B.K.S. (My University, 2019)
The paper introduces the actuation requirements of an active tendon concept that is being developed under the Horizon 2020 SABRE project (Shape Adaptive Blades for Rotorcraft Efficiency). The basic idea of the concept is to incorporate a tensile structural member (referred to as a tendon) into a rotorcraft blade to introduce a means of controlling the blade’s effective stiffness and hence its dynamic properties. This control mechanism should ensure that potentially harmful rotor resonances in various flight regimes are effectively and adaptively avoided. In previous studies, free vibration analysis for the blade-tendon system was conducted numerically and validated against non-rotating experiments. The resulting models are used here to support conceptual design and sizing of the tendon loading system. The actuation requirements in terms of the actuator force, stroke, power and other measures are discussed for simplified representations of the Bo105, Lynx XZ170 and EH101 helicopter rotor blades. It is shown that electro-mechanical linear actuator technology offers realizable loading approach and nominal peak loads of around 6 kN allow adaptive decrease of the in-plane and out-of-plane bending natural frequencies between 0.05/rev and 0.2/rev.